KEEFEKTIFAN MODEL PEMBELAJARAN TIME TOKEN TERHADAP KETERAMPILAN BERBICARA SISWA SMK XYZ PALEMBANG - Octarina, Ayu (Smart Education, 2025)
Abstract: This study aims to determine the effectiveness of the Time Token learning model on the speaking skills of students at SMK XYZ Palembang. The research method used is a quasi-experimental study. The results showed that the average value of the initial test of the experimental class was 49.55 and the control class was 47.75, while the average value of the final test of the experimental class was 72.55 and the control class was 64.19. Thus, Ha which reads